Reaction of rat connective tissue to implanted dentin tube filled with mineral trioxide aggregate, Portland cement or calcium hydroxide. - Holland, Roberto [UNESP]; Souza, Valdir de [UNESP]; Nery, Mauro Juvenal [UNESP]; Faraco Júnior, Italo Medeiros; Bernabé, Pedro Felício Estrada [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP] (My University, 2001)
The subject of this study was to observe the rat subcutaneous connective tissue reaction to implanted dentin tubes filled with mineral trioxide aggregate, Portland cement or calcium hydroxide. The animals were sacrificed after 7 or 30 days and the undecalcified specimens were prepared for histological analysis with polarized light and Von Kossa technique for mineralized tissues. The results were similar for the studied materials. At the tube openings, there were Von Kossa-positive granules that were birefringent to polarized light. Next to these granulations, there was an irregular tissue like a bridge that was Von Kossa-positive. The dentin walls of the tubes exhibited in the tubules a structure highly birefringent to polarized light, usually like a layer and at different depths. The mechanism of action of the studied materials has some similarity.
Keywords: aluminum derivative; calcium derivative; calcium hydroxide; coloring agent; diagnostic agent; fluorescent dye; mineral trioxide aggregate; oxide; silicate; tooth cement; animal; cell nucleus; chemically induced disorder; connective tissue; dentin; drug combination; drug effect; fibroblast; giant cell; human; neutrophil; pathology; polarization microscopy; rat; skin; time; tooth pulp disease; ultrastructure; Aluminum Compounds; Animals; Calcium Compounds; Calcium Hydroxide; Cell Nucleus; Coloring Agents; Connective Tissue; Dental Cements; Dentin; Dentin, Secondary; Drug Combinations; Fibroblasts; Fluorescent Dyes; Giant Cells; Humans; Microscopy, Polarization; Neutrophils; Oxides; Rats; Silicates; Skin; Time Factors